2017
DOI: 10.1016/j.lwt.2017.05.030
|View full text |Cite
|
Sign up to set email alerts
|

The influence of ecophysiological factors on growth, aflR gene expression and aflatoxin B1 production by a type strain of Aspergillus flavus

Abstract: Maize is prone to infection by Aspergillus flavus, which can contaminate the product with aflatoxins. The objective of this study was to examine the impact that interactions between water activity (aw) and temperature may have on growth, the expression of a biosynthetic regulatory gene (aflR) and aflatoxin B1 (AFB1) production by a strain of A. flavus on a maize-based medium. Results showed that there were some differences between lag phases and growth rates of A. flavus. The optimum growth rate for A. flavus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 39 publications
1
27
0
Order By: Relevance
“…Further, Gallo et al [ 84 ] reported high expression of the aflR and aflS regulatory genes under conditions non-conducive for aflatoxin production. Likewise, in a more recent study, Bernáldez et al [ 85 ] found a weak correlation between the expression level of aflR and aflatoxin production. The authors demonstrated that aflR expression is not a good indicator for aflatoxin production in A. flavus .…”
Section: Factors Affecting Fungal Growth and Mycotoxin Production In mentioning
confidence: 90%
“…Further, Gallo et al [ 84 ] reported high expression of the aflR and aflS regulatory genes under conditions non-conducive for aflatoxin production. Likewise, in a more recent study, Bernáldez et al [ 85 ] found a weak correlation between the expression level of aflR and aflatoxin production. The authors demonstrated that aflR expression is not a good indicator for aflatoxin production in A. flavus .…”
Section: Factors Affecting Fungal Growth and Mycotoxin Production In mentioning
confidence: 90%
“…Aspergillus flavus , for example, is associated with Aspergillus infections of grain crops in the field; it also contaminates stored grains when prevailing abiotic factors (such as temperature and water activity) are favourable [ 3 , 4 ]. Interactions between environmental stress factors, such as water activity and temperature, may have an influence on growth, expression of biosynthetic regulatory genes and mycotoxin production by mycotoxigenic fungal species [ 5 , 6 ]. Good postharvest practices avoiding high temperatures and rapid drying of grain can avoid a decrease in the grain quality and reduce the health risk due to mould growth and potential toxin contamination [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interactions between environmental stress factors, such as water activity and temperature, may have an influence on growth, expression of biosynthetic regulatory genes and mycotoxin production by mycotoxigenic fungal species [ 5 , 6 ]. Good postharvest practices avoiding high temperatures and rapid drying of grain can avoid a decrease in the grain quality and reduce the health risk due to mould growth and potential toxin contamination [ 6 ]. Poor postharvest management can lead to rapid deterioration in quality, with severe decreases in germinability and nutritional value of stored grain, possibly accompanied by undesirable fungal contamination and, consequently, toxin production [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mycelia were removed from half the surface of the dry-cured ham cubes and frozen quickly in liquid nitrogen, it was stored at −80 • C until the extraction of RNA. RNA was extracted using the commercial kit RNeasy ® plant mini kit (QIAGEN, Madrid, Spain) [52]. For this, the mycelia were mixed with 500 µL of lysis solution buffer containing 10 µL of β-mercaptoethanol and then processed according to the manufacturer's instructions.…”
Section: Rna Extractionmentioning
confidence: 99%
“…Two primers (Table 4) were used to amplify the β-tubulin gene, which was used as an endogenous control [52]. For the relative expression of the genes otapksPN and otanpsPN involved in the biosynthesis of OTA, two pairs of primers were used [19,52].…”
Section: Primers Usedmentioning
confidence: 99%